METHOD OF CALCULATION NEUTRON FLUX IN FLAT MEDIUM - Hayrapetian, I. N.; Martoyan, G. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
This paper presents a method for calculating the neutron flux in a plane medium by solving the neutron transport equation using Legendre polynomial approximation. The results demonstrate the advantage of this method over the previous method.